O corpo como palco da teatralidade humana: marcas na formação acadêmica - Amaral, Augusto Luis Medeiros (2009)
This piece of writing intends to contribute to the concept of human theatricality, corporifying itself while memories and experimentations are stated. It is a process of development inspired on the philosophy of difference, the device of which is the theater. It tries to make bodies that Interact, transformations, markings, dispersions evident, providing elements that compose a group of practice-theory.Actions and ideas generated during incursions in alien territory, at the frontier among art, philosophy, and education in a changing zone. The empirical field of research is constituted fundamentally from the experience of teaching Educational Philosophy and The Philosophy of Physical Education in the undergraduate course of Physical Education, at the Atlântico Sul College, understood here as the practice of Oneself. Work developed around the recognition of the processes of development of its agents, questioning the formal field of education, the ditional relation between the subject and the object of research, the hegemonic models, and the finished product.The field of problem making appears from the resistance to living and defines the methodological pathway of research.